2017
DOI: 10.1002/tesj.322
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Culturally and Linguistically Competent Teachers for English as an International Language Education

Abstract: Despite recent scholarly advancements in teaching English as an international language (EIL), its implementation in TESOL classrooms has been challenging and limited. Because English teachers play a significant role in EIL implementation in their daily lessons, preparing EIL-oriented teachers becomes critical. This article outlines major developments in EIL and their implications for teacher competence and discusses the ideological challenges in integrating EIL in teacher education. It concludes with a detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…With our intention to examine the issues of multilingual and multicultural awareness presented by the literacy teacher‐educators, we fill a gap in the research about how teacher‐educators who demonstrate these elements of awareness can support diverse student populations, as well as in‐service teachers, within the context of partnerships in K‐12 literacy classrooms. As research has shown, while many teachers can effectively use generalised pedagogical approaches to address the cultural and linguistic needs of CLDs (Gay, ; Li, ), they must also be able to use these pedagogies within specific content areas, such as English language arts and reading, mathematics, science, and social studies (see Gay, ). Learning about the awareness of language and culture that teacher‐educators demonstrate when supporting literacy, and specifically, writing instruction, is critical for enabling in‐service teachers to address students’ diverse needs in this subject area.…”
Section: Awareness Of Language and Culturementioning
confidence: 99%
“…With our intention to examine the issues of multilingual and multicultural awareness presented by the literacy teacher‐educators, we fill a gap in the research about how teacher‐educators who demonstrate these elements of awareness can support diverse student populations, as well as in‐service teachers, within the context of partnerships in K‐12 literacy classrooms. As research has shown, while many teachers can effectively use generalised pedagogical approaches to address the cultural and linguistic needs of CLDs (Gay, ; Li, ), they must also be able to use these pedagogies within specific content areas, such as English language arts and reading, mathematics, science, and social studies (see Gay, ). Learning about the awareness of language and culture that teacher‐educators demonstrate when supporting literacy, and specifically, writing instruction, is critical for enabling in‐service teachers to address students’ diverse needs in this subject area.…”
Section: Awareness Of Language and Culturementioning
confidence: 99%
“…Teacher educators who come to understand and respond to cultural differences need time, space, openness to change, multilingual and multicultural awareness, as well as experiences with practice, boundary-crossing, and transformational learning (de los Ríos & Souto-Manning, 2015;D'Haem & Griswold, 2017;Dixson & Dingus, 2007;Han, 2016;Howe & Xu, 2013;Merryfield, 2014;Smith, , 2018Williams & Berry, 2016). Despite variability in teacher educators' responsiveness (Li, 2017), research indicates they are also better able to relate to students when they know more about language and culture by developing awareness of difference in their teaching practices (Costa et al, 2005;.…”
Section: Literature Review: Educators' Responsiveness To Cultural And...mentioning
confidence: 99%
“…This notion, along with Ladson-Billing's articulation of culturally sustaining pedagogy, allowed us to consider the "multiplicities of identities and cultures that help formulate today's youth culture" (Ladson-Billings, 2014, p. 82;Paris, 2012), as well as the "within-group" and "across-group" cultural practices necessary for cultural competence (Paris, 2012, p. 95). In conjunction, linguistically responsive pedagogy-the use of guidelines for integrating principles of learning with principles of language to support students' language difference (see Lucas & Villegas, 2013)-provided a lens to examine educators' pedagogical responsiveness to students and teachers' literacy needs across a range of linguistic groups (e.g., Li, 2017;Lucas & Villegas, 2013).…”
Section: Culturally Relevant Culturally Sustaining and Linguistically...mentioning
confidence: 99%
“…The next article, ‘Implementing EIL paradigm in ELT classrooms’ by Ali, however, shows satisfactory evidence of a paradigm shift in the attitudes among Malaysian teachers. Putting these studies in consecutive chapters is significant in that the revealed perception differences among teachers working in varying cultural contexts helps raise readers’ awareness that a key first step towards the implementation of an EIL paradigm is to explore the attitudes that teachers hold as to this perspective, since they are the key agents in translating EIL principles into ELT classrooms (Li, 2017).…”
mentioning
confidence: 99%